(untitled) (Polis (Santiago), 2019)
This paper seeks to address the nexus mobility, borders and security in relation to the recent historical journey of Haitian migration in South America, highlighting for this the role played by states in the processes of securitization, illegalization and criminalization of international migration. The objectives are aimed at deepening the study of the emergency conditions, practical effects and fundamentals through which the visa policy is implemented in Brazil, Chile and, with special emphasis, in the Argentine national framework. In this sense, a qualitative methodology was adopted that included the analysis of documentary statistical reports, regulations and journalistic notes that refer, in a localized manner, to the visa policy addressed to persons of Haitian nationality in each of the mentioned countries. The study reveals how certain national groups are incorporated into the security agenda through selective state practices that, under similar security and humanitarian control arguments, position the visa as a fundamental mechanism for the regulation of migratory movements across borders.